Signalling process during the early contact of ectomycorrhizal fungi Pisolithus tinctorius with Castanea sativa roots - Baptista, Paula (2011)
Ectomycorrhizas (ECM) are symbiotic associations between roots of higher plants, mainly trees (e.g. Pinacea and Fagaceae), and soil fungi (asco- and basidiomycetes). The establishment of this symbiotic association requires a sequence of highly regulated and coordinated events, initiated by an exchange of specific signalling compounds between both partners.